2014
DOI: 10.1161/atvbaha.113.302806
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein 55B Is a Novel Regulator of Cellular Cholesterol Metabolism

Abstract: Objective Inter-individual variation in pathways impacting cellular cholesterol metabolism can influence levels of plasma cholesterol, a well-established risk factor for cardiovascular disease. Inherent variation among immortalized lymphoblastoid cell lines (LCLs) from different donors can be leveraged to discover novel genes that modulate cellular cholesterol metabolism. The objective of this study was to identify novel genes that regulate cholesterol metabolism by testing for evidence of correlated gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…9e ). In agreement with the report by Medina et al 48 , we observed that the upregulation of TMEM55B induced by U18666A was significantly decreased in cells depleted of SREBF2 (Fig. 7f ); however, the decrease was even more pronounced in cells depleted of SREBF2, TFEB, and TFE3 (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…9e ). In agreement with the report by Medina et al 48 , we observed that the upregulation of TMEM55B induced by U18666A was significantly decreased in cells depleted of SREBF2 (Fig. 7f ); however, the decrease was even more pronounced in cells depleted of SREBF2, TFEB, and TFE3 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…A previous study suggested that the levels of TMEM55B are modulated by the transcription factor SREBF2 in response to cholesterol levels 48 . In agreement with this report, we found that in HeLa cells, sterol depletion by treatment with a combination of lipo-protein depleted serum and statins caused a significant TMEM55B upregulation both to the mRNA and protein levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that PIP5Kα knockdown significantly decreased whole cell PIP2 levels by 30% in RAW264.7 cells (Figure 5 I). Conversely, we knocked down Tmem55b, a specific PIP2 phosphatase that converts PIP2 to PI5P and has a role in cellular cholesterol metabolism 41 , whose expression we detected in RAW264.7 cells (Online Figure VIII A). This knockdown modestly, but significantly, increased cellular apoA1 binding, cholesterol efflux to apoA1, and whole cell PIP2 levels (Online Figure VIII B-D).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed four times. Effects of RP1-13D10.2 overexpression on media levels of APOB were quantified by ELISA as previously described 21 . To measure the effect of RP1-13D10.2 overexpression on LDLR transcript stability, Huh7 cells were transfected for 48 hours with either the pCMV6-entry plasmid or the RP1-13D10.2 overexpression plasmids, treated with 1 μg/mL actinomycin D and harvested over 6 hours.…”
Section: Methodsmentioning
confidence: 99%